Desert locusts in the Caribbean. Proceedings of a regional meetign port of Spain, Trinidad and Tobago november 16th, 1988 - Stemshorn, Barry (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Series Miscellaneous Publication A2/TT (IICA) no. 89-01.